The Prevalence, Characteristics, and Relationship of Risk Factors in Upper GI Tract Bleeding Patients Undergoing Endoscopy in Dr. Doris Sylvanis General Regional Hospital in 2019–2020 - Muhammad Andrean Syahridho; Lia Sasmithae; Austin Bertilova Carmelita (The Indonesian Journal of Gastroenterology, Hepatology and Digestive Endoscopy)
Background: Upper gastrointestinal bleeding occurs in the lumen from the proximal section of the Treitz ligament. Furthermore, it is divided into variceal and non-variceal bleeding based on the etiology. The risk factors include age, smoking, alcohol, portal hypertension, hepatitis, and medications. Upper GI bleeding manifests as hematemesis and melena. This study aims to determine the prevalence, characteristics, and relationship of risk factors with upper GI bleeding in patients undergoing endoscopy in Dr. Doris Sylvanus General Regional Hospital Palangka Raya in 2019–2020.